The pipB Gene as Target for Development of Detection Method of Pathogenic Bacteria Salmonella typhi Using Real-time Polymerase Chain Reaction - Nurjayadi, Muktiningsih; Gusti Angieta Putri; Ananda Indah Putri Sihombing; Puan Aqila Azizah; Anisa Fitriyanti; Royna Rahma Musie; Helzi Angelina; Grace; Agus Setiawan; Dandy Akbar Juliansyah; Jefferson Lynford Declan; Gladys Indira Putri; Siti Fatimah; Adinda Myra Amalia Putri; Vira Saamia; Irma Ratna Kartika; Fera Kurniadewi; Shyi-Tien Chen; Bassam Abomoelak; Hesham A. El Enshasy (Bogor Agricultural University, Indonesia, 2025)
Salmonella typhi is a bacteria that leads to typhoid fever and one of the causes of death due to bacteria infections. In Indonesia, typhoid fever occurs around 1,100 cases per 100,000 population per year, with a mortality rate of 3.1-10.4%. It's necessary to develop a rapid and accurate detection of Salmonella typhi. The pipB gene of Salmonella typhi has the function of being an autophagia inhibitor in humans. This study aims to develop a detection kit for Salmonella typhi pathogenic bacteria targeting the pipB gene using a pipB primer in confirmation, specificity, and sensitivity tests. The results showed that pipB primer can amplify Salmonella typhi DNA fragment of 196 bp at the optimum annealing temperatures between 54-62°C. Confirmation test with real-time PCR found that the pipB primer pair (pipB-F and pipB-R) amplified at cycle 12.93 and 13.10 (Duplo) with a Tm value of 84.05°C and 84.20°C (Duplo). Based on the difference and average value produced in the confirmation and specificity test, pipB primer has amplified Salmonella typhi DNA at Ct 12.47±0.6 with a Tm value of 83.62°C±0.6. The pipB primer pair (pipB-F and pipB-R) could distinguish target from non-target bacteria based on their cycle threshold (Ct) and melting temperature (Tm) values. The primer design of pipB primer pair (pipB-F and pipB-R) successfully detected Salmonella typhi bacteria with the smallest concentration of 55.78 × 102 CFU equivalent to 3.2 pg/µL. Based on the results, Salmonella typhi pipB primer successfully detected Salmonella typhi bacteria DNA rapidly, specifically, and sensitively using the real-time polymerase chain reaction method.